# How do you solve the equation #6x^2-5x-13=x^2-11# by completing the square?

##### 1 Answer

Aug 20, 2017

#x=sqrt(13/20)+1/2#

#x=-sqrt(13/20)+1/2#

#### Explanation:

Given -

#6x^2-5x-13=x^2-11#

Take all the terms to the left-hand side

#6x^2-5x-13-x^2+11=0#

Simplify it.

#5x^2-5x-2=0#

Take the constant term to the right-hand side

#5x^2-5x=2#

Divide all the terms by the coefficient of

#(5x^2)/5-(5x)/5=2/5#

#x^2-x=2/5#

Take half the coefficient of

#x^2-x+1/4=2/5+1/4=(8+5)/20=13/20#

#(x-1/2)^2=13/20#

#(x-1/2)=+-sqrt(13/20)#

#x=sqrt(13/20)+1/2#

#x=-sqrt(13/20)+1/2#